17% efficient printable mesoscopic PIN metal oxide framework perovskite solar cells using cesium-containing triple cation perovskite. Issue 44 (1st November 2017) - Liu, Shungshuang; Huang, Wenchao; Liao, Peizhe; Pootrakulchote, Nuttapol; Li, Hao; Lu, Jianfeng; Li, Junpeng; Huang, Feihong; Shai, Xuxia; Zhao, Xiaojuan; Shen, Yan; Cheng, Yi-Bing; et al.
Abstract : Cs0.05 (FA0.4 MA0.6 )0.95 PbI2.8 Br0.2 based devices showed an impressive efficiency of 17.02% and excellent thermal stability with long electron and hole diffusion lengths. Abstract : Fully printable perovskite solar cells (PSCs) based on an inorganic metal oxide architecture have attracted tremendous attention due to its feature of showing principally high stability. However, fully printable PSCs show a lower power conversion efficiency (PCE) than the thin film PSCs owing to the thick mesoscopic layers that pose an obstacle to charge collection. Herein, the triple cation perovskite Cs0.05 (FA0.4 MA0.6 )0.95 PbI2.8 Br0.2, for the first time, is introduced in fully printable PSCs on the basis of a mesoporous metal oxide TiO2 /Al2 O3 /NiO layered framework with a carbon counter electrode. We found that partial replacement of FA/MA by Cs could increase the bandgap and exciton binding energy of Cs x (FA0.4 MA0.6 )1− x PbI2.8 Br0.2 perovskite. An optimal efficiency of 17.02% can be obtained using Cs0.05 (FA0.4 MA0.6 )0.95 PbI2.8 Br0.2 as the light absorber under AM 1.5G 100 mW cm −2 light illumination, which, to the best of our knowledge, represents the highest efficiency observed to date for fully printable PSCs using a carbon counter electrode. Detailed investigations with nanosecond transient absorption spectroscopy and transient photovoltage/photocurrent decay measurements revealed that the presence of Cs in perovskite compounds can increase the charge carrier lifetime along with diffusion length, benefiting charge transport in thick mesoscopic layers. Furthermore, the Cs0.05 (FA0.4 MA0.6 )0.95 PbI2.8 Br0.2 -based PSCs exhibit good stability with a retention of over 90% initial PCE after 1020 h in dark conditions at 85 °C.